Man lär sig inte språket i skolan, man måste lära det överallt. : Några meänkielilärares tankar om meänkieli och dess framtid - Erkheikki, Mervi (Umeå universitet, Institutionen för språkstudier, 2017)
The purpose of this study is to find out about meänkieli teachers' attitudes towards the language they are teaching. This interview study is concentrated on three main issues; education, attitudes and the future of meänkieli. The teachers seem to be positive towards their work, even though there are a lot of issues that need to be improved, for example the lack of textbooks. The attitudes of the surrounding enviroment seem to be more positive the further away one gets from the area where meänkieli is mainly spoken. The teachers are hopefull but hesitant about the future of meänkieli and its preservation for the future generations.